DIGITAL COMIC STRIP AS AN ATTEMPT FOR SELF-CONTROL AGAINTS IMPULSIVE BUYING AMONG GENERATION Z - Ghea Sonja Imanda; Siswo Martono; Evi Farsiah Utami (Gorga : Jurnal Seni Rupa, 2024)
Generation Z has a close relationship with social media, which influences the emergence of Fear of Missing Out (FOMO). Uncontrolled FOMO can result in a lifestyle that prioritizes wants over needs. This type of lifestyle eventually has an impact on impulsive buying behaviors often seen in Generation Z. To prevent impulsive buying in Generation Z, good self-control is necessary. Based on this, the research aims to design a digital comic strip as an effort for self-control and prevention of impulsive buying in Generation Z. The digital comic strip is designed to send educative informations for the target audience. The research uses a qualitative method and the design process using a design thinking method. The results of the data collection in the form of observations, interviews, documentation, and literature studies indicate that many Generation Z have engaged in impulsive buying. In addition, data collection also shows that Generation Z is interested and easily accepts information from digital comic strips because of the simple language, easily understandable content, easy access, and attractive features, such as illustration style, character design, and story flow. Therefore, it is concluded that a digital comic strip is needed that can be used as an effort for Generation Z's self-control over impulsive buying.